2010
DOI: 10.1007/s00114-010-0751-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological distinctness despite large-scale phenotypic plasticity—analysis of wild and pond-bred juveniles of allopatric populations of Tropheus moorii

Abstract: Cichlids are an excellent model to study explosive speciation and adaptive radiation. Their evolutionary success has been attributed to their ability to undergo rapid morphological changes related to diet, and their particular breeding biology. Relatively minor changes in morphology allow for exploitation of novel food resources. The importance of phenotypic plasticity and genetically based differences for diversification was long recognized, but their relationship and relative magnitude remained unclear. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…This result stands in contrast to the fact that cichlids exhibit phenotypic plasticity in a number of different traits (Meyer ; Kerschbaumer et al. ; Machado‐Schiaffino et al. ).…”
Section: Discussionmentioning
confidence: 72%
“…This result stands in contrast to the fact that cichlids exhibit phenotypic plasticity in a number of different traits (Meyer ; Kerschbaumer et al. ; Machado‐Schiaffino et al. ).…”
Section: Discussionmentioning
confidence: 72%
“…Phenotypic plasticity is described as the environmentally sensitive production of alternative phenotypes by given genotypes (DeWitt and Scheiner ). Plasticity is a common phenomenon in cichlids and laboratory experiments have confirmed the ability of many cichlid species to change the jaw apparatus in response to different diets (Witte ; Hoogerhoud ; Meyer ; Wimberger ; Huysseune ; Smits et al ; Bouton et al ; Stauffer and Van Snik Gray ; Kerschbaumer et al ; Muschick et al ; Gunter et al ), although different diets in the wild do not always lead to divergence in morphology in cichlids (see Odhiambo et al ). Some of these studies tested plasticity of the premaxilla and showed a shorter ascending arm and a larger angle β of the premaxilla as a phenotypic response to a feeding style involving manipulation of prey (especially biting, Witte ; Wimberger ; Bouton et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In all four species, we found a shorter ascending arm and in P. degeni , the species with the most robust premaxilla, which indicates a biting‐like feeding style, a larger angle β. Recent plasticity experiments on Lake Tanganyika cichlids, three‐spined sticklebacks, and Trinidadian guppies have shown morphological responses resembling adaptive phenotypes evolved under natural conditions (Kerschbaumer et al ; Torres‐Dowdall et al ; Wund et al ). These studies all suggest that phenotypic plasticity might play an important role in the colonization of novel environments, which we think is likely to be the case for Lake Victoria cichlids.…”
Section: Discussionmentioning
confidence: 99%
“…One alternative, reproductive character displacement, that is, the increase of isolation between taxa that are already good species (as opposed to reinforcement), seems less likely, given that all distinctive traits have a plausible ecological background. According to the six check-criteria for character displacement suggested by Grant (1972) and Arthur (1982) and considering the remarks of Schluter and McPhail (1992), the following evaluation can be made: Chance can be ruled out as an explanation of the pattern, given that other cases of sympatry also constitute the same depth segregation of the two entities.According to pond-breeding experiments (Kerschbaumer et al. , 2011; Koch et al , 2012), the phenotypic differences among populations in sympatry and allopatry have a genetic basis, on top of plasticity.…”
Section: Discussionmentioning
confidence: 99%